MITOS KESEMPATAN SETARA DAN REPRODUKSI KETIMPANGAN SOSIAL: Potret Konkret Ketidakadilan Sosial dalam Pendidikan bagi Anak-anak Petani Tambak di Wilayah Pinggiran Indramayu - Sahrudin, Sahrudin (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The Universal Declaration of Human Rights in 1948 states that every individual has the right to education. Therefore, education must be accessible to everyone regardless of differences in ethnicity, social status, geographic location, religion, political views, or physical and mental conditions. This highlights that every child should have equal opportunities to receive education. The success of education in Indonesia is generally measured by two aspects: the teaching and learning process, and the outcomes, which are evaluated based on competencies. To achieve this success, educational tools are required, including both human resources (teachers) and non-human resources. However, there is a significant gap between education in urban and rural areas, including in the outskirts. One example is the education of children of fish farmers in the outskirts of Indramayu city. Is it true that schools provide equal opportunities for all children, or is this merely a myth? In reality, social inequality is reproduced through the education system. Does the school system benefit students from higher social classes more? What is the condition of education for the children of fish farmers in the outskirts of Indramayu? Their education in Cantigi Village, Indramayu, falls far below acceptable standards. Even the learning facilities are not comfortable enough for students to gain knowledge. This situation is worsened by the lack of educational facilities to support successful learning, in stark contrast to schools in urban areas. At the primary level, this is the critical time for children to develop their cognitive, affective, and psychomotor skills. This reality aligns with Pierre Bourdieu's critique that schools function as institutions that reproduce social inequality. According to Bourdieu, social inequality in education is particularly evident when comparing the chances of entering higher education: students from upper social classes have an 80% chance, while those from farmer and laborer backgrounds have only a 40% chance.